The Adsorption and Diffusion Manners of Hydrogen Atoms on Pt (100), Pt (110), and Pt (111) Surfaces - Vurdu, Can Doğan (Wiley, 2018)
In this study, the interactions between H atoms and the (100), (110), and (111) surfaces of platinum have been investigated by using the London-Eyring-Polanyi-Sato (LEPS) potential function. The adsorption zones (sites) and LEPS energy values of these sites have been determined theoretically. In addition, the potential-energy surfaces for each Pt surface have been obtained in detail. Further, the adsorption sites on the surface, scattering from the surface, diffusion paths on the surface, and transition regions to the subsurface, have been determined and the differences have been examined in detail among the surfaces. From these results, it is found that an H atom has the lowest binding energy at the hollow sites on the Pt (100) and Pt (111) surfaces and that it has the lowest binding energy at the long-bridge sites on the Pt (110) surface. It has also been determined that the hollow sites on the three surfaces are the regions through which H atoms can penetrate into the subsurface. In addition, it has also been found that, for each of the three Pt surfaces, the diffusion of an H atom across the surface may follow a bridge-hollow-bridge pathway. These results are in agreement with previous experimental and theoretical results. Besides, the adsorption and diffusion manners of hydrogen atoms on each of the Pt surfaces have been analyzed deeply.
Keywords: Physics; QC1-999; 13. Climate action; 3. Good health